Factors predicting conversion from colon capsule endoscopy to conventional optical endoscopy—findings from the CESCAIL study - Ian Io Lei; Ioanna Parisi; Anirudh Bhandare; Francisco Porras Perez; Thomas Lee; Chander Shehkar; Mary McStay; Simon Anderson; Angus Watson; Abby Conlin; Rawya Badreldin; Kamran Malik; et al. (BMC Gastroenterology)
Abstract Background Colon capsule endoscopy (CCE) has become an alternative to traditional colonoscopy for low-risk patients. However, CCE's low completion rate and inability to take biopsies or remove polyps often result in a CCE-to-conventional colonoscopy conversion (CCC). Objective(s) The aim is to identify the factors that predict issues with bowel cleansing, capsule excretion rates, pathology detection, and the need for CCC. Methods This prospective study analysed data from patients who underwent CCE as part of the CESCAIL study from Nov 2021 till June 2024. Predictive factors were examined for their association with CCC, including patient demographics, comorbidities, medications, and laboratory results from symptomatic and surveillance groups. Statistical methods such as LASSO, linear, and logistic regression were applied. Results Six hundred and three participants were analysed. Elevated f-Hb levels (OR = 1.48, 95% CI:1.18–1.86, p = 0.0002) and smoking (OR = 1.44, 95% CI: 1.01–2.11, p = 0.047) were significantly associated with CCC. The area under the curve (AUC) of elevated f-Hb for predicting CCC was 0.62 after adjusting for confounders. Diabetes was linked to poor bowel preparation (OR = 0.40, 95%CI:0.18–0.87, p = 0.022). Alcohol (p = 0.004), smoking (p = 0.003), psychological conditions (p = 0.001), and haemoglobin levels (p = 0.046) were significantly associated with the number of polyps, whilst antidepressants (p = 0.003) and beta-blockers (p = 0.001) were linked to the size of polyps. Conclusion Non-smokers with lower f-Hb levels are less likely to need conventional colonoscopy (CCC). Patient selection criteria are key to minimising the colonoscopy conversion rate. Our findings would benefit from validation in different populations to develop a robust CCE Conversion Scoring System (CECS) and ultimately improve the cost-effectiveness.